Independent and Combined Effects of Antioxidant Supplementation and Circuit Resistance Training on Selected Adipokines in Postmenopausal Women - Saeidi, Ayoub; Jabbour, Georges; Ahmadian, Mehdi; Abbassi-Daloii, Asieh; Malekian, Fatemeh; Hackney, Anthony C.; Saedmocheshi, Saber; Basati, Gholam; Ben Abderrahman, Abderraouf; Zouhal, Hassane (Frontiers in Physiology, 2019)
We examined the effects of the independent and combined effects of Zataria multiflora supplementation and circuit resistance training (CRT) on selected adipokines among postmenopausal women. Forty-eight postmenopausal women were divided into 4 groups: Exercise (EG, n =12), Zataria multiflora (ZMG, n =12), exercise and Zataria multiflora (ZMEG, n =12), and control (CG, n=12). Participants in experimental groups either performed CRT (3 sessions per week with intensity at 55% of one-repetition maximum) or supplemented with Zataria Multiflora (500mg every day after breakfast with 100 ml of water), or their combination, for 8 weeks. Blood samples were collected at pre- and post-intervention for measuring selected adipokines, including visfatin, omentin-1, vaspin, FGF-21, adiponectin, leptin, and ghrelin. Our findings demonstrated that visfatin, vaspin, and leptin levels significantly decreased over the intervention period (all P < .05), with these values were lower in EG and ZMEG in comparison to CG at post-intervention (all P < .05). Visfatin and vaspin levels were also lower in ZMEG in comparison to EG at post-intervention (both P < .05). In contrast, omentin-1, gherlin, adiponectin, and FGF21 significantly increased in EG and EMG (all P < .05) after CRT. These finding suggest that Zataria Multiflora supplementation by itself has little effect on measured adipokines, however, its combination with CRT produced noticeable effects on circulating levels of these adipokines, even more than CRT alone. Consequently, combination of CRT and Zataria Multiflora supplementation may represent a potentially beneficial non-pharmacologic intervention on some selected adipokines in postmenopausal women.